(untitled) (REMUNOM, 2026)
This work describes the development of a multichannel digital thermometer to validate the temperature control of giant unilamellar vesicle (GUVs) electroformation equipment. The prototype presented was built with cheap and conventional resources, such as elements and circuits from the Arduino open-source platform and negative temperature coefficient (NTC) thermistors, resulting in equipment with good precision, low production cost and easy maintenance. The device allows temperature measurement in four channels simultaneously and records the values on the computer for temporal evaluation. This equipment was essential in the process of creating a GUV electroforming device discussed elsewhere, but there are several possibilities for application in the research and development of other temperature-dependent technologies. In particular, the device allowed the development of the GUV electroformation protocol by identifying the delay process caused by positioning the thermometer outside the studied sample.